Impact of CEO Overconfidence on Capital Structure Decisions: Evidence from S&P BSE 200. Issue 1 (February 2023) - Mundi, Hardeep Singh
The article presents the impact of CEO overconfidence on capital structure decisions for Indian firms. Using a sample of S&P BSE 200 companies between 2000 and 2015, this study presents results using regression models on the panel data. The findings of this study highlight the significance of behavioural bias of CEO overconfidence to better understand capital structure decisions. This study found that overconfident CEOs prefer debt financing over equity financing and such overconfident CEOs prefer short-term debt over long-term debt. The behavioural features of CEOs are crucial for board of directors, especially in designing the compensation packages. The robustness of results using multiple proxies corroborates previous finding of western nations and shows that CEOs' overconfidence plays an important role for CEOs of developing nations too.